REVIEW OF BASIC IMMUNIZATION SERVICES AT LOK BAHU HEALTH CENTER JANUARI-JULI 2025 - Rahmania; Aprilia Nurlaila Zahro; Wa Ode Nurul Azkiah; Ainaya Salsabila; Hanis Kusumawati Rahayu; Zulhijrian Noor (Mulawarman International Conference on Tropical Public Health, 2025)
Complete basic immunization (CBI) is a priority public health program aimed at preventing Vaccine-Preventable Diseases (VPDs). This study aimed to review the implementation of CBI services at Lok Bahu Health Center, Samarinda City, during the period of January–July 2025. This research employed a descriptive qualitative design involving key informants (health workers and posyandu cadres) and supporting informants (health center management, pharmacy staff, and parents). Data were collected through in-depth interviews, observation, documentation, and review of official records, then analyzed through data reduction, data display, and conclusion verification using source, method, and data triangulation. The findings revealed that at the planning stage, the program was arranged through the Annual Activity Proposal Plan (RUK) and cross-sectoral coordination; however, specific strategies to reach hard-to-reach populations were still limited, community involvement remained suboptimal, and non-vaccine funding relied heavily on cadres’ self-sufficiency. At the implementation stage, the main obstacles included limited health personnel and cadres, delays in vaccine distribution, and community resistance to immunization. From the beneficiaries’ perspective, parents’ time constraints and concerns about vaccine side effects also affected the completeness of child immunization. At the evaluation stage, the Mini Quarterly Workshops functioned as forums for identifying barriers and cross-sectoral follow-up, yet discrepancies persisted between manual recording and the ASIK digital application, alongside reporting delays from posyandu. In conclusion, CBI coverage in the Lok Bahu Health Center working area has not met the national target, influenced by planning, implementation, and evaluation factors that have not been fully integrated. Strengthening cross-sectoral coordination, funding support, stable vaccine distribution, adaptive risk communication, and synchronization of digital recording systems are required to sustainably improve immunization coverage.